Development of tacrine clusters as positively cooperative systems for the inhibition of acetylcholinesterase. (1st January 2021) - Evangelista, Tereza Cristina Santos; López, Óscar; Ferreira, Sabrina Baptista; Fernández-Bolaños, José G.; Sydnes, Magne O.; Lindbäck, Emil
Abstract: The synthesis of four tetra-tacrine clusters where the tacrine binding units are attached to a central scaffold via linkers of variable lengths is described. The multivalent inhibition potencies for the tacrine clusters were investigated for the inhibition of acetylcholinesterase. Two of the tacrine clusters displayed a small but significant multivalent inhibition potency in which the binding affinity of each of the tacrine binding units increased up to 3.2 times when they are connected to the central scaffold.